2009
DOI: 10.1038/nmeth.1398
|View full text |Cite
|
Sign up to set email alerts
|

Imaging neural activity in worms, flies and mice with improved GCaMP calcium indicators

Abstract: Genetically encoded calcium indicators (GECIs) can be used to image activity in defined neuronal populations. However, current GECIs produce inferior signals compared to synthetic indicators and recording electrodes, precluding detection of low firing rates. We developed a single-wavelength GECI based on GCaMP2 (GCaMP3), with increased baseline fluorescence (3x), dynamic range (3x), and higher affinity for calcium (1.3x). GCaMP3 fluorescence changes triggered by single action potentials were detected in pyrami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

48
1,983
8
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 1,805 publications
(2,042 citation statements)
references
References 45 publications
48
1,983
8
3
Order By: Relevance
“…[3][4][5][6][7][8] Nevertheless, though a useful correlation often exists between Ca 2+ dynamics and neuronal spiking across a range of spike frequencies, the slowkinetics and saturation of [Ca 2+ ]-related fluorescent signals constrain the utility of Ca 2+ imaging as a means of probing spiking dynamics in many neuron types. 4,9 Numerous voltage-sensitive indicators 1,[10][11][12][13][14][15][16][17][18] permit direct imaging of cellular membrane potentials. Organic voltage-sensitive dyes have allowed functional mapping studies in awake mammals 14 and studies of individual cells' dynamics in invertebrates 19 and mammalian brain slices.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7][8] Nevertheless, though a useful correlation often exists between Ca 2+ dynamics and neuronal spiking across a range of spike frequencies, the slowkinetics and saturation of [Ca 2+ ]-related fluorescent signals constrain the utility of Ca 2+ imaging as a means of probing spiking dynamics in many neuron types. 4,9 Numerous voltage-sensitive indicators 1,[10][11][12][13][14][15][16][17][18] permit direct imaging of cellular membrane potentials. Organic voltage-sensitive dyes have allowed functional mapping studies in awake mammals 14 and studies of individual cells' dynamics in invertebrates 19 and mammalian brain slices.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, there was no pathological nuclear translocation of the sensor in hippocampal CA1 neurons of mice from age postnatal day 13 to 6-month-old animals. By contrast, studies on long-term expression of several GECIs by adeno-associated virus-mediated gene transfer recently reported progressing cytomorbidity and concomitant restricted localization of the sensor to the cell nucleus 11 . Thus, transgenic expression of calcium biosensors is likely to be more suitable for long-term expression of indicators.…”
Section: Discussionmentioning
confidence: 91%
“…In addition, we investigated whether long-term expression of TN-XXL could cause changes in cell morphology. In a previous study a pathological aggregation of several GECIs to the nucleus was reported after longterm adeno-associated virus vector-mediated expression in cortical neurons 11 . Here, we looked at 13 days, 36 days, 2-month-and 6-month-old brains from TN-XXL transgenic mice and performed confocal images of frozen sections of the CA1 and CA3 region of the hippocampus ( Supplementary Fig.…”
Section: Widespread Expression Of Tn-xxl In Transgenic Micementioning
confidence: 91%
See 1 more Smart Citation
“…In addition, by using tissue specific promoters and selective cellular targeting modifications, these proteins became most useful for calcium signaling analysis within selected tissues, specific cell types or intracellular compartments (see Refs. [13][14][15][16][17]). In most cases, under proper expression conditions, GECIs have minimum effects on cellular activity, can be used in vivo as well, and therefore are also suitable for long-term studies (see Ref.…”
Section: Methods For Studying Calcium Signals In Human Ps Cellsmentioning
confidence: 99%